(untitled) (Scottish Historical and Archaeological Internet Reports, 2006)
This section presents summaries of small-scale archaeological investigations within the south transept in 1981, during installation of new organ in 1990-91, around the north transept in 1991 and during reflooring of the choir in 1993.